(untitled) (Research, Society and Development, 2021)
Osteomas are benign osteogenic tumors, which clinically manifest as well-defined and asymptomatic lesions. This article aims to report a case of extensive osteoma in the mandibular branch, addressing the main tools used for diagnosis and treatment modalities. Patient L.M.S, 55 years old, male, sought the service of Maxillofacial Surgery, reporting the appearance of a nodule on the face with evolution of 2 years. On physical examination, a significant volumetric increase was observed in the pre-auricular region on the left side, asymptomatic on palpation and non-bleeding. Computed tomography was requested, which showed a hyperdense bone lesion in the mandibular ramus region. The planned surgical proposal was for extra-oral access in the pre-auricular region on the left side, excision of the lesion by osteotomy followed by osteoplasty for the regularization of the remaining bone tissue and suture by planes. Subsequently, the piece was sent for histopathological analysis that identified the lesion as a compact osteoma. The patient was followed up for 1 and a half years, through clinical and radiographic evaluation, through which an excellent bone repair was observed, with no signs of recurrence. Carrying out the clink exam is essential for the diagnosis of osteoma, as it is an asymptomatic pathology. Due to the fact that it has a low probability of recurrence and does not present malignancy, a conservative approach can be performed with the appropriate postoperative follow-up. Therefore, it is concluded that the performance of a thorough clinical examination associated with the imaging and microscopic information are essential for a good clinical management of this pathology.